1959
DOI: 10.1002/j.1537-2197.1959.tb06976.x
|View full text |Cite
|
Sign up to set email alerts
|

FACTORS AFFECTING THE VERTICAL DISTRIBUTION OF RHIZOCTONIA SOLANI WITH SPECIAL REFERENCE TO CO2 CONCENTRATION

Abstract: Durbin, Richard D. (U. Minnesota, St. Paul.) Factors affecting the vertical distribution of Rhizoctonia solani, with special reference to CO2 concentration. Amer. Jour. Bot. 46(1) : 22‐25. Illus. 1959.—Thirty‐three heterogeneous clones of 3 ecological types of Rhizoctonia solani (aerial, surface, and subterranean, based on their vertical distribution on the host plant) were grown in flowing atmospheres containing various levels of CO2. The linear growth rates were compared with those obtained when the clones w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

1960
1960
1989
1989

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(3 citation statements)
references
References 5 publications
0
3
0
Order By: Relevance
“…Burges (2) suggested that CO2 might be of greater consequence in determining population modifications in poorly aerated cir cumstances than 02, a slight increase in pC02 frequently having a more marked influence upon fungi than the corresponding decrease in pOt. This suggestion is supported by the observation that subterranean strains of Rhizocfonia solani are more tol erant of CO2 than strains whose chief si te of activity is near the soil surface, whereas isolates of this pathogen that attack aerial portions of susceptible plants exhibit the greatest sensitivity (61), the particular habitat seemingly selecting for the predominating R. solani types. Pathogenicity of the fungus is diminished by CO2, moreover, a factor of possible rel evance to investigations of the biological control of soil-borne pathogens (62).…”
Section: Biochemical Influence Of the Environment On Microorganismsmentioning
confidence: 71%
See 1 more Smart Citation
“…Burges (2) suggested that CO2 might be of greater consequence in determining population modifications in poorly aerated cir cumstances than 02, a slight increase in pC02 frequently having a more marked influence upon fungi than the corresponding decrease in pOt. This suggestion is supported by the observation that subterranean strains of Rhizocfonia solani are more tol erant of CO2 than strains whose chief si te of activity is near the soil surface, whereas isolates of this pathogen that attack aerial portions of susceptible plants exhibit the greatest sensitivity (61), the particular habitat seemingly selecting for the predominating R. solani types. Pathogenicity of the fungus is diminished by CO2, moreover, a factor of possible rel evance to investigations of the biological control of soil-borne pathogens (62).…”
Section: Biochemical Influence Of the Environment On Microorganismsmentioning
confidence: 71%
“…For example, organic acids commonly liberated during the growth of bacteria and fungi have been detected in soil, and cer tain of the acids were found to inhibit the growth of fungi, especially in acid conditions (71,97) . Carbon dioxide, the concentration of which may become quite high particularly within the microenvironment, is also concerned in amensalistic interactions, altering not only the biochemical activity of indi vidual s pecies but also the composition of the microbial co mmunity at the site of CO2 accumulation (61,62) . Ammonia formed in nitrogen mineraliza tion is a potent inhibitor for Nitrobacter in alkaline habitats, the toxicity being governed by both the pH and the ammonia concentration (98) , and the nitrite that remains by virtue of the repression of nitrite-oxidizing auto trophs may, in turn, affect the survival or biochemical activities of sensitive fungi.…”
Section: Interactions Among Microorganisms In the Soil Environmentmentioning
confidence: 99%
“…The pathogenic phase was even-more sensitive to carbon dioxide than the active saprophytic stage. Durbin (1959) found that clones of Rhizoctonia foimd in the soil were more tolerant to carbon dioxide than those found in aerial environments. Certain Fusariian and Trichoderma spp.…”
Section: Discnssiosmentioning
confidence: 98%